Oxidative Stress and Gene Expression Modifications Mediated by Extracellular Vesicles: An In Vivo Study of the Radiation-Induced Bystander Effect - Rita Hargitai; Dávid Kis; Eszter Persa; Tünde Szatmári; Géza Sáfrány; Katalin Lumniczky (MDPI AG, 2021)
Radiation-induced bystander effect is a biological response in nonirradiated cells receiving signals from cells exposed to ionising radiation. The aim of this in vivo study was to analyse whether extracellular vesicles (EVs) originating from irradiated mice could induce modifications in the redox status and expression of radiation-response genes in bystander mice. C57BL/6 mice were whole-body irradiated with 0.1-Gy and 2-Gy X-rays, and EVs originating from mice irradiated with the same doses were injected into naïve, bystander mice. Lipid peroxidation in the spleen and plasma reactive oxygen metabolite (ROM) levels increased 24 h after irradiation with 2 Gy. The expression of antioxidant enzyme genes and inducible nitric oxide synthase 2 (iNOS2) decreased, while cell cycle arrest-, senescence- and apoptosis-related genes were upregulated after irradiation with 2 Gy. In bystander mice, no significant alterations were observed in lipid peroxidation or in the expression of genes connected to cell cycle arrest, senescence and apoptosis. However, there was a systemic increase in the circulating ROM level after an intravenous EV injection, and EVs originating from 2-Gy-irradiated mice caused a reduced expression of antioxidant enzyme genes and iNOS2 in bystander mice. In conclusion, we showed that ionising radiation-induced alterations in the cellular antioxidant system can be transmitted in vivo in a bystander manner through EVs originating from directly irradiated animals.